The role of special program in sports in the athletic activities and performance of student-athletes in physical education - Lobo, Joseph (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
The role of sports in education has been very evident across various educational institutions. Based on the previously conducted studies, it has been recognized as a builder of solid intellect for students. However, only a few investigations were found concerning the role of SPS in the development of student-athletes’ athletic activities and performance in Physical education in a local setting here in the Philippines; hence, the conduct of the study regarding this matter is highly recommended. In connection to this, the present study aims to determine the role of the Special Program in Sports (SPS) in the athletic activities and performance of student-athletes in physical education. This study utilized a self-made questionnaire where inputs were taken from the related literature and studies reviewed and adapted to the Coaching Behavior Scale for Sport (CBS-S). Moreover, part of the questionnaire dealt with the coaching commitment and physical development of student-athletes involving the 4Cs (caring, character, competence, and connection). Descriptive and regression analyses were utilized to interpret data gathered from the respondents. The results have shown that the level of SPS was found to be very high in terms of instructor/coach, sports event, sports facilities, and training schedule. Also, the level of athletic activities was reported as high concerning training performance, regular sports participation, and health status, and very high in regards to theoretical knowledge, athletic potential, focus and discipline, resiliency and humility, and harmony and unity. SPS has been found to have no significant effect on the athletic activities and performance of student-athletes. Recommendations for the improvement of coaches and student-athletes, and future research to support the findings of this study are presented.